Psychiatric and legal considerations for ketamine treatment within prison settings - Bayrhammer-Savel, Michael; Ortner, Martin; Van Hout, Marie-Claire; Komorowski, Arkadiusz (Frontiers in Psychiatry, 2024)
The fundamental right to equivalence of health care in prison settings encompasses the provision of medication to address mental health conditions. Considering the increased risk for self-harm among individuals dealing with depression, the limited effectiveness of conservative antidepressants is a major challenge in psychiatry. The high prevalence of suicidal tendencies within prison populations underscores the imperative for state-of-the-art pharmacological treatment to uphold adequate health care standards. Notably, the denial of access to effective medication could be deemed a violation of human rights of people living in prison according to international treaties, domestic law, and United Nations normative standards of detention. This article presents the authors’ perspective on the accessibility of ketamine treatment in prison settings, discussing psychiatric and legal considerations as well as current challenges in this context. Implementing novel psychopharmacological interventions may alleviate the distress experienced by individuals struggling with depressive symptoms and suicidality. At the same time, unprecedented treatment alternatives bring along potential issues, including limited understanding of long-term effects and the risk of abuse. Given the scarce data-availability, a pressing need exists for further research on the benefits and risks of ketamine treatment within prison populations.